A comparative study on the fracture toughness of two heavy-bodied glass ionomer cements and microhybrid composite - Chua, Jett Jerard Joan J.; Sunit, Mariel V.
Tooth colored restorations are a staple in today's practice. In the advent of modern technology, manufacturers are continuously developing a material that would satisfy the need for superior mechanical properties along with excellent esthetics and ease of use. The aim of this study was to compare the fracture toughness of two heavy bodied glass ionomer cements and a microhybrid composite. Five specimens each of Ketac Molar, Fuji IX and Filtek Z250 were prepared using the American Standard for Testing Materials guidelines. Samples were stored at a maintained temperature of 37 (± 1) °C for 24 ±1 hours and were subjected to 3 point loading in a UTM. The load upon fracture was recorded. Results showed that Ketac Molar and Fuji IX are comparable to each other in terms of fracture thoughness. Clinically, these can be utilized alternately in areas where flexural strength is needed. Filtek Z250, on the other hand, presented a significant mechanical advantage over the two glass ionomer cements and remains to be the material of choice.
Thesis--(Doctor of Dental Medicine)--University of the Philippines Manila
Keywords: Dental glass ionomer cements; Dental materials; Composite resins